What (really) makes a country nuclear? Insights from nonnuclear Southeast Asia. Issue 1 (2nd January 2016) - Abraham, Itty
Abstract : Beginning with the question 'what makes a country nuclear?', this article goes on to argue that nuclearity is produced by the powerful formulations of a 'totalitarian' nuclear discourse. To break out of this conceptual box, I explore the nuclear histories of two seemingly nonnuclear countries, Thailand and Philippines, adopting a genealogical approach to the study of nuclear power. Paying close attention to the 'insurrection of subjugated knowledges' permits breaking down the boundaries between the nuclear establishment and the rest of society and shows the close and mutually reinforcing ties between nuclear power and other forms of state power. The case of Thailand shows how nuclear power reflects the unequal distribution and illegitimacy of state power, while the Philippines story demonstrates how the failure of a major nuclear project can lead to the collapse of an authoritarian state. I conclude that nuclear power is only deemed 'exceptional' when scholarship refuses to acknowledge nuclear power as a heterogeneous social apparatus grounded within a particular political context.